Attendence monitoring system via RFID / Zainirah Abdul Manan - Abdul Manan, Zainirah (Faculty of Computer and Mathematical Sciences, 2007)
The existing system only uses punch card. The administration cannot manage the database efficiently and systematic. The admin also need more time to check the attendance one by one. Attendance Monitoring System via FRID will help to solve this problem. The solution is developing Attendance Monitoring System via RFID equipment for FTMSK’s staff. The scope is limit of distance because passive tags have practical read distances ranging from 0 to 10 cm using the RFID reader. The information of lecturer in database is limited only less than thousand users and using web camera to get a static image. A description research design using a survey instrument was administered in this study. To gather more information from the subjects, the methodology that was used in this study is using system development life cycle (SDLC). In doing this system, the methodologies are totally implemented in order to ensure the research done in phase by phase manner. After that, implement the system to get the result. This system has developed to monitor the attendance monitoring system via RFID, it is ability easy and proper manages the attendance, save time and prevent buddy punching. From the literature search will help to gain knowledge to develop the system. It helps in the convergence speed and the result is better.